A Study of the Lack of Slow Magnetic Relaxation in Mononuclear Trigonal Bipyramidal Cobalt(II) Complexes. Issue 4 (21st January 2021) - Świtlicka, Anna; Machura, Barbara; Cano, Joan; Lloret, Francesc; Julve, Miguel
Abstract: Two complexes of formula [Co(H2 tba)(N3 )]⋅MeOH (1 ) and [Co(H2 tba)(NCS)] ⋅ 2DMF (2 ) [H3 tba=tris(2‐benzimidazolylmethyl)amine] were prepared and characterized aiming at investigating the influence of the structural and chemical effects on the Ising‐type magnetic anisotropy in mononuclear trigonal bipyramidal cobalt(II) complexes. Each cobalt(II) ion in 1 is five‐coordinate by a monodentate azide ligand and a tetradentate monodeprotonated H2 tba ‐ group building a slightly distorted trigonal bipyramidal surrounding. Compound 2 is also a mononuclear species whose structure was previously reported and only some of its structural data are considered in this work for comparative purposes. Detailed dc and ac cryomagnetic measurements of 1 and 2 show the lack of slow magnetic relaxation both in the presence and absence of applied dc fields. The profile of the χM T against T plots together with the non‐superimposable M against H/T curves for 1 and 2 support the occurrence of high‐spin Co(II) ions with an appreciable magnetic anisotropy. Q‐band EPR studies on polycrystalline samples of these compounds at low temperatures confirm the positive value of the zero‐field splitting ( D ), a strong asymmetry in the g ‐tensors and hence an easy plane of magnetization indicating stabilization of M S =±1/2 sublevels of the S =3/2 spin state. A comparison of our results with previous magneto‐structural reports on mononuclear trigonal bipyramidal cobalt(II) complexes that exhibit slow relaxation of the magnetization is carried out in order get deeper insights about the electronic and structural factors that would be at the origin of the lack of Single‐Ion Magnet (SIM) behaviour for 1 and 2 . Abstract : Study of lack of slow magnetic relaxation in two trigonal bipyramidal complexes of formula [Co(H2 tba)(N3 )]⋅MeOH and [Co(H2 tba)(NCS)] ⋅ 2DMF based on the monodeprotonated form of the scorpionate, tetradentate tris(2‐benzimidazolylmethyl)amine ligand. Both Co(II) compounds exhibit axial g ‐anisotropy and positive D values whose sign is confirmed by EPR spectroscopy. They do not display SIM behavior in contrast to what occurs with the few previously reported examples of this family that having positive D values exhibit slow relaxation of the magnetization.